Development of a running speed game model for teaching short-distance running at telaga biru public elementary school 16 - Mohamad Syawal; Aishah R Pomatahu; Juni Isnanto (Jambura Arena Sport, 2025)
This study is a Research and Development (RD) study developed using the ADDIE model, comprising five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Direct-instruction teaching of short-distance running at SD Negeri 16 Telaga Biru has produced low student interest, limited active participation, and underdeveloped starting, acceleration, and coordination technique, representing a clear pedagogical gap that this study addresses by embedding sprint training within a competitive relay-game structure. This research aimed to develop and evaluate the feasibility and effectiveness of a Running Speed game model for teaching athletics to elementary school students. Data were collected through expert validation questionnaires (learning experts and game experts) and a pretest-posttest field trial involving fourth-grade students. Expert validation indicated that the product falls into the “feasible to highly feasible” category in terms of material suitability, movement-activity appropriateness, safety, and clarity of instructions. Field implementation produced a significant positive impact on students’ cognitive, psychomotor, and affective learning outcomes. The novelty of this study lies in its systematic integration of relay-based competitive play with the technical demands of short-distance running (start, acceleration, and sprint) within a validated ADDIE development cycle evaluated across three learning domains simultaneously. These findings support confidence that the Running Speed model is a feasible and empirically effective alternative for athletics instruction in resource-limited elementary schools.